To obtain the equivalent value of the expression, the following steps are necessary:
Step 1: Rewrite the expression and substitute the value of x and y, as follows:
![\frac{2x^2+y^2\text{ }}{3}](https://img.qammunity.org/2023/formulas/mathematics/college/co7na3u9eour0l3m5vrerwb1smukc06xs5.png)
Now, since x = 1.5 and y = 3, we have:
![\begin{gathered} \frac{2x^2+y^2\text{ }}{3} \\ \Rightarrow\frac{2(1.5)^2+(3)^2\text{ }}{3} \\ \Rightarrow\frac{2(2.25)^{}+(9)^{}\text{ }}{3} \\ \Rightarrow\frac{4.5^{}+9^{}\text{ }}{3} \\ \Rightarrow\frac{13.5^{}\text{ }}{3} \\ \Rightarrow4.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r579stuswtovypp6p7ito1xecousxa6brr.png)
Therefore, the equivalent value of the expression is 4.5